Pengaruh Kinerja Penyuluh Pertanian Lapangan dan Pemanfaatan Teknologi Digital terhadap Peningkatan Kapasitas Petani di Era Digital pada Badan Penyuluhan dan Pengembangan Sumber Daya Manusia Pertanian Kementerian Pertanian - Surahman Surahman (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The agricultural sector is undergoing rapid transformation in the digital era, yet disparities in farmers’ capacity and the performance of agricultural extension workers remain significant challenges. This study aims to examine the effect of agricultural extension workers’ performance and the utilization of digital technology on improving farmers’ capacity within the Agricultural Extension and Human Resources Development Agency of the Ministry of Agriculture. A quantitative approach was employed using a survey method involving 72 farmers selected through incidental sampling. Data were collected using structured questionnaires that had passed validity and reliability testing. Multiple linear regression analysis was applied using SPSS to evaluate the relationships among variables. The results indicate that both the performance of agricultural extension workers and the utilization of digital technology have a positive and significant effect on farmers’ capacity. The regression coefficients show that extension performance contributes slightly more compared to digital technology utilization. Furthermore, the coefficient of determination (R² = 0.547) suggests that these two variables explain a substantial proportion of the variance in farmers’ capacity. These findings highlight the importance of strengthening extension services alongside expanding digital technology adoption to enhance farmers’ knowledge, skills, and adaptive capacity in the digital era.